Big Data: Challenges por Public Policy - Sosa Escudero, Walter (Revista del CLAD Reforma y Democracia, 2020)
This article explores the phenomenon of big data and its potential for use in the public sector. It argues that big data is not just “more of the same”, but that it face challenges that can open the door to the enormous advantages in the use of algorithms and massive data, guaranteeing to the citizens that its less desirable effects will not appear. A scientific perspective is adopted to emphasize the enormous potential of big data, its main limitations, and, most importantly, the intermediate arena formed by challenges and uncertainties typical of a dynamic and still unstable phenomenon.
Keywords: Informatics; Information Technology; Communication Engineering; Public Policy; Public Sector; Perspectives